Neurovascular management of intracranial internal carotid artery dissection post-carotid endarterectomy: A case report of an innovative approach - Bibhas Amatya; Ameet V. Chitale; Dipankar Mukherjee (Brain Circulation)
Carotid endarterectomy (CEA) is an established method of stroke prevention in patients with severe carotid artery stenosis, especially in those with symptomatic disease. Complications of CEA include perioperative stroke, cranial nerve palsy, hemorrhage, and vascular dissection. We present an unusual case of a 66-year-old man who presented for elective right CEA for symptomatic 70% right internal carotid artery (ICA) stenosis due to ulcerated plaque. Following surgery, the patient developed fluctuating neurological deficits consistent with involvement of the right middle cerebral artery territory. Imaging revealed possible mild clamp-induced ICA dissection limited to the ICA in the neck. Despite initial successful anticoagulation management in the neurointensive care unit, the patient returned 2 days later with stroke symptoms, necessitating urgent endovascular intervention. Neurovascular interventions involved aspiration thrombectomy and multiple stenting extending distally into intracranial ICA, which successfully restored cerebral arterial perfusion and normal neurological function. This case highlights the first reported instance of extensive intracranial ICA dissection managed with full-length stenting. This article offers an effective endovascular procedure for preventing a devastating stroke from a complication of a procedure that was performed to prevent it.